Analysis of Product Development for Jempol Coffee Brand in Natar District - Ahmad Redho; Riswan Riswan (Cita konsultindo, 2024)
The quality of customer service plays a crucial role in the success of an organization, especially in the energy sector such as PT. PLN (Persero). This study aims to analyze the role of human resource management (HRM) in improving the quality of customer service at PT. PLN (Persero) Unit Pelaksana Pelayanan Pelanggan (UP3) Tanjung Karang. The research method used is a survey with questionnaires distributed to employees and customers of PT. PLN (Persero) UP3 Tanjung Karang. The results show that HRM has a significant impact on the quality of customer service. Factors such as recruitment, training, and employee development have a positive relationship with customer satisfaction. Additionally, internal communication, employee motivation, and reward systems also play a crucial role in improving employee performance and directly contribute to the quality of service provided to customers. This research contributes to understanding the close relationship between HRM and the quality of customer service in the energy industry context. The practical implications of this research can assist PT. PLN (Persero) UP3 Tanjung Karang in optimizing HRM strategies to enhance customer satisfaction and maintain competitiveness in the competitive energy market. The conclusion of this research provides a basis for similar companies to better understand the importance of HRM in achieving strategic goals related to the quality of customer service.